Knowledge of life - Canguilhem, Georges, 1904-1995 (Fordham University Press, 2008)
As the work of thinkers such as Michel Foucault, François Jacob, Louis Althusser, and Pierre Bourdieu demonstrates, Georges Canguilhem has exerted tremendous influence on the philosophy of science and French philosophy more generally. In Knowledge of Life, a book that spans twenty years of his essays and lectures, Canguilhem offers a series of epistemological histories that seek to establish and clarify the stakes, ambiguities, and emergence of philosophical and biological concepts that defined the rise of modern biology. How do transformations in biology and modern medicine shape conceptions of life? How do philosophical concepts feed into biological ideas and experimental practices, and how are they themselves transformed? How does knowledge "undo the experience of life so as to help man remake what life has made without him, in him or outside of him?" Knowledge of Life is Canguilhem's effort to explain how the movements of knowledge and life come to rest upon each other. Published at the dawn of the genetic revolution and still pertinent today, the book tackles the history of cell theory, the conceptual moves toward and away from mechanical understandings of the organism, the persistence of vitalism, and the nature of normality in science and its objects.